Prevalence of serological ineligibility among blood donors of a hemotherapy center in Caxias do Sul, Southern Brazil - Cattani, Fernanda; Ril, Heloisa; Paludo, Crislaine Aparecida; Leite, Márcia Araújo (Clinical and Biomedical Research, 2017)
Introduction: Blood donation should be voluntary, anonymous and altruistic, and the donor should not, directly or indirectly, receive any remuneration or benefit by virtue of donating blood. Like any other therapeutic method, transfusion procedures are not risk free and can expose the patient to a several complications. Serological screening is of great importance to ensure transfusion safety. The present study aimed to estimate the prevalence of serological ineligibility among blood donors from a Hemotherapy Center in Caxias do Sul (RS). Method: An exploratory, descriptive and quantitative study was conducted on data from July 2010 to December 2015 collected at a Hemotherapy Center in Caxias do Sul (RS). Results: During the study period, 14,267 blood donors attended the Hemotherapy Center, of which 9,332 (65.40%) were males and 4,935 (34.60%) were female. Considering only the suitable donors, 12,702 blood donations were performed, 144 (1.13%) presented positive serological tests. The most prevalent positive serology was for hepatitis B (anti-HBc) with 98 cases (0.77%), followed by syphilis with 19 cases (0.15%); Chagas disease, with 10 (0.08%); hepatitis C, with nine (0.07%); and HIV and HTLV, with four (0.03%) reactive samples each. Conclusion: The results presented are important for health surveillance and make it possible to take measures to ensure safe blood stocks. Keywords: Serology, blood donors, communicable diseases.